(untitled) (Journal of Science and Technology Research, 2024)
The export-oriented Garment sector has made crucial contribution to the transformation of the Bangladesh economy. The number of garment industry is now about 5560 and provides employment to as many as 5.0 million workers. Job stress is one of the common problems that employees confront with increasing frequency. Recently job stress is becoming an epidemic in the work environment. This cross sectional study was carried out on a sample of 418 garment workers selected by non-probability sampling technique from two garment factories. The study was done from 1st July 2021 to 30th June 2022 with an objective to assess the level of job stress and related factors in garment workers. Job stress was estimated by using Occupational stress index (OSI) questionnaire; while socio-demographic, behavioral and work related information were obtained using semi structured questionnaire. Among 418 respondents, 71% were female and 21% were male, their mean age was 29.35±6.185 & they were mostly married (72%). 45.2% had no formal education The mean family income and individual income were Tk.13181.07±4826.598 & Tk.6812.10±1029.504 respectively. Among the respondents, 64.4% belong to cutting/sewing section, 79.2% of them were employed for 1 to 5 years & mean duration of employment was 3.78±3.083 years. Among respondents, 69.9% had moderate stress followed by 17% having low stress and 13.2 % with high stress. Among 12 subscale the mean scores of under participation (mean score = 4.33) and responsibility for person (mean score =4.22) was higher. It was found that monthly income and compulsory work over time produce odds ratio 0.401, 11.963 respectively. This indicates every additional unit of monthly income, respondents were 0.401 times less likely to develop job stress (OR=.401) and every additional unit of compulsory overtime, respondents were 11.963 times more likely to develop job stress (OR=11.963). There was a significant association of job stress and gender, smoking habit, monthly income and work overtime. Measures to be taken to alleviate these stressors which can promote the worker in greater contribution in their profession. J. of Sci. and Tech. Res. 5(1): 163-168, 2023